Environmental Impact and Carbon Footprint Assessment of Sustainable Buildings: An Experimental Investigation - Naga Dheeraj Kumar Reddy Chukka; A. Arivumangai; Sanjeev Kumar; R. Subashchandrabose; Yeddula Bharath Simha Reddy; L. Natrayan; Geleta Chala Debela (Adsorption Science & Technology)
Carbon emission has been considerably higher in India in the last few decades. The greenhouse gases increased to an imaginary volume, a major contributor to global warming. Chennai is one of India’s large cosmopolitan cities, contributing more Gross Domestic Product (G.D.P.) and carbon to the atmosphere. The infrastructure sector is always a booming sector in and around Chennai, which requires more construction materials. In turn, the construction of new buildings expands the city with a large area of urban and suburban Chennai, where I.T. division, automobile division, and industrial estates are available. Hence, this study deals with the carbon emission of a residential building constructed with conventional materials in and around Chennai. So, one can estimate the emission of carbon by the conventional building, which leads to global warming and climate change.